2006
DOI: 10.1007/s11240-006-9093-3
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of carnation with genes related to ethylene production and perception: towards generation of potted carnations with a longer display time

Abstract: Potted carnation (Dianthus caryophyllus L. cv. Lillipot) plants were transformed with cDNAs for carnation 1-aminocyclopropane-1-carboxylate (ACC) synthase (DC-ACS1, s/aACS transgenes) or ACC oxidase (DC-ACO1, s/aACO transgenes) in sense or antisense orientation or mutated carnation ethylene receptor cDNA (DC-ERS2¢) by Agrobacterium-mediated gene transfer. The presence of acetosyringone at 100 lM in media for shoot culture prior to leaf explant preparation and preculture of Agrobacterium in addition to the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…An introduction of the ACO gene in antisense orientation has been proved as an efficient method for ethylene suppression and is still in use (Nuñez-Palenius et al 2006;Kinouchi et al 2006;Huang et al 2007;Wang et al 2009). Other studies have demonstrated that the introduction of truncated ACO gene constructs in the sense orientation can result in co-suppression of homologous host genes, and modulate ethylene biosynthesis (Knoester et al 1997;Aida et al 1998;López-Gómez et al 2009).…”
Section: Altering Ethylene Levels In Plants Via Acomentioning
confidence: 99%
“…An introduction of the ACO gene in antisense orientation has been proved as an efficient method for ethylene suppression and is still in use (Nuñez-Palenius et al 2006;Kinouchi et al 2006;Huang et al 2007;Wang et al 2009). Other studies have demonstrated that the introduction of truncated ACO gene constructs in the sense orientation can result in co-suppression of homologous host genes, and modulate ethylene biosynthesis (Knoester et al 1997;Aida et al 1998;López-Gómez et al 2009).…”
Section: Altering Ethylene Levels In Plants Via Acomentioning
confidence: 99%
“…Bovy et al 95 introgressed an Arabidopsis thaliana etr1-1 allele into carnation gemone to generate transgenic lines, where its heterologous expression reduced ethylene production and enhanced flower longevity. Kinouchi et al 96 generated transgenic lines in potted carnation harbouring ACC oxidase (DCACO1, s/aACO) or ACC synthase (DC-ACS1, s/aACS) in sense or antisense orientation, or mutated carnation ethylene receptor cDNA (DC-ERS2). Inokuma et al 97 observed reduced ethylene production and longer vase life in the transgenic lines of 'Lillipot' carnation harbouring an sACO transgene.…”
Section: Carnation (Dianthus Caryophyllus)mentioning
confidence: 99%